Arthroscopically Assisted Reduction of Sagittal-Plane Disruption of Distal Tibiofibular Syndesmosis - Sin, Yiu Ho (Arthrosc Tech, 2019)
Injuries to the distal tibiofibular syndesmosis can occur in conjunction with ankle fractures. Sagittal instability of the syndesmosis is more critical than coronal instability and must be taken into account when considering reduction and fixation of the syndesmosis. The purpose of this Technical Note is to report the technique of arthroscopically assisted reduction of sagittal-plane disruption of the distal tibiofibular syndesmosis. This ensures a comprehensive assessment of the pattern of syndesmotic disruption, which can aid anatomic reduction of the syndesmosis.